The effects of Tualang honey with or without diet modifications on sperm profile in high cholesterol diet induction animal model - Hasan, Sakiinah; Abdul Rahim, Roslina; Alias, Mohd Afzal; Muhammad, Siti Aeshah @ Naznin; Abdullah, Nor Zamzila; Abdul Razak, Redzuan Nul Hakim (2021)
Introduction: Hypercholesterolaemia is a recognised factor associated with male infertility. However, currently, there is limited therapy available. Tualang honey (TH) is a type of Malaysian polyfloral wild honey produced by the rock bee (Apis dorsata) that has been proven to exert both anti-inflammatory and anti-oxidative effects. This study aimed to determine the effects of TH with or without diet modifications on the sperm profile high cholesterol diet (HCD) administered rats. Methods: Thirty Sprague Dawley rats weighing 200 - 250 gm were randomly divided into the standard diet (control) group (n=6), mixed cholesterol diet (MCD) group and high cholesterol diet (HCD) group (n=12 each). The six rats in the control group were fed with standard commercial rat pellet while the 12 rats in the MCD and HCD group were fed with a 12% cholesterol diet for 16 weeks. At the end of the 16 weeks, the rats in the MCD group were divided into two subgroups (M1 and M2) and continued on standard diet in addition to administration of distilled water and 1.2 g of honey per kg body weight daily respectively for 4 weeks. The rats in the HCD group were divided into two subgroups (H1 and H2) and continued on the 12% high cholesterol diet in addition to administration of distilled water and 1.2 g of honey per kg body weight daily respectively for 4 weeks. The rats in the control group were continued with commercial rat pellets without honey supplementation. At the end of the 4 weeks, all rats were sacrificed and the cauda epididymis was collected for sperm analysis. Results: The sperm parameters (sperm concentration, the percentage of total sperm motility, progressive motility, normal sperm morphology, and viability) of rats in group M1 and H1 were significantly reduced compared to the control. In contrast, all TH supplemented groups demonstrated significant improvement in the sperm parameters. However, there were significant increase in the sperm concentration and normal sperm morphology in group M2 compared to H2. Conclusion: In conclusion, the TH supplementation with diet modifications improved the sperm analysis results in the animal model.